The Mimesis Hierarchy of semiotic development: Five stages of intersubjectivity in children - Zlatev, Jordan (Public Journal of Semiotics, 2013)
The paper proposes that intersubjectivity develops in children along a progression of five, more or less distinct, stages of semiotic development. The theoretical model within which this is couched is the Mimesis Hierarchy (MH) model (Zlatev & Andrén 2009). As in previous treatments, the MH-model focuses on bodily mimesis, its ―precursors‖ (empathetic perception) and ―post-developments‖ (conventionality, language and narrative). Mimesis is pivotal since it provides the basis for the development of (i) conventions (through imitation), (ii) intentional communication, and (iii) for bringing the two together in communicative, shared representations (signs). The main difference from previous applications is in the treatment of the concepts of representation and communicative intent. Due to recent empirical findings, and a more bodily-enactive and social-oriented perspective, I propose that Stage 2 gives rise to imitation and mimetic schemas (Zlatev 2007, in press), but that the first gestures (or vocalizations) of children are neither externalizations of these "internal representations", nor fully-fledged representations/signs on their own, but action schemas bidirectionally associated with particular contexts. That would explain why the onset of intentional communication occurs in Stage 3 with pointing and other deictic gestures (such as showing), which are not representations or fully-fledged (explicit) signs, but rather performative communicative acts, accompanied with makers of communicative intent. It is first in Stage 4 that the proto-representations of Stage 2 and the communicative intent of Stage 3 are combined to give rise to communicative iconic gestures, and more generally to the "insight" of using communicative, shared representations, or what is commonly referred to as symbols or signs.